The pathological and therapeutic roles of mesenchymal stem cells in preeclampsia - Sanshan Jin; Sanshan Jin; Canrong Wu; Ming Chen; Dongyan Sun; Hua Zhang; Hua Zhang (Frontiers in Medicine, 2022)
Mesenchymal stem cells (MSCs) have made progress in the treatment of ischemic and inflammatory diseases. Preeclampsia (PE) is characterized by placenta ischemic and inflammatory injury. Our paper summarized the new role of MSCs in PE pathology and its potency in PE therapy and analyzed its current limitations. Intravenously administered MSCs dominantly distributed in perinatal tissues. There may be additional advantages to using MSCs-based therapies for reproductive disorders. It will provide new ideas for future research in this field.